Kinetic, electrochemical and spectroscopic investigation of the oxidation of CO and C2H4 on YSZ-supported metal model electrodes - Bachmann, Christoph; Justus Liebig University Giessen (My University, 2015)
In this study we investigated the in& #64258;uence of an electrochemical potential on the surface properties of solid cells and thereby on the development of switchable solid cells and electrocatalysts. A key point of this work has been the investigation of the so-called NEMCA effect (Non-faradaic Electrochemical Modi& #64257;cation of Catalytic Activity) or EPOC effect (Electrochemical Promotion of Catalysis) which explains the modi& #64257;cation of the reaction rate of a catalytic reaction like CO or ethylene oxidation by application of an electrochemical potential on a metal electrode placed on an ion conducting solid electrolyte. The effect is generally explained by the migration of charged ions (spillover species) originating from the electrolyte onto the surface of the catalyst thereby modifying the surface properties. The focus of this work has been drawn on the combination of spectroscopic and microscopic methods with electrochemical techniques to get a deeper understanding into the NEMCA effect and the nature of the electrochemical created spillover species. The utilization of model electrodes with geometric well de& #64257;ned and spectroscopic accessible electrode surfaces (triple phase boundary (TPB) length) were of importance. Besides the build-up of the setup to measure the catalytic activity of solid cells and the accompanied measurements of the in& #64258;uence of an applied potential on the reaction rate the spectroscopic and microscopic techniques have been re& #64257;ned to a point where a coupling with electrochemical methods is possible and changes on the surface and the TPB can be monitored in-situ. The following measurements have been conducted in detail: Characterization of different electrode types and different electrode materials on different orientated substrate materials in reference to sinter effects. X-Ray Diffraction (XRD, pol& #64257;gure measurements), Scanning Electron Microscopy (SEM), Electron Backscatter Diffraction (EBSD) show oxidation and de-wetting effects depending on the material combined with grain growth and reduction of different orientated grains. Electrochemical investigations of Pt/YSZ and Ag/YSZ cells under high vacuum conditions with and without reactive gases have been done. The results reveal a storage of oxygen at the metal/YSZ interface and a small (persistent) NEMCA effect. Kinetic measurements for different Pt electrodes in the presence of CO and O2 reveal a strong in& #64258;uence of the TPB length for the kinetic behavior and the overall conversion. Additionally a strong in& #64258;uence of the underlying substrate could be found. Electrochemical investigations under different NEMCA typical conditions for different temperatures have been done. The results show that a NEMCA effect is only visible after pro-longed heat treatment. Due to the thermodynamic stability of platinum and platinum oxide a change between both states upon temperature treatment is likely. An obtained metastable state upon decreasing temperature can be destabilized by electrochemical polarization therefore showing a NEMCA effect. Surface XRD (S-XRD) measurements have been conducted to identify the conditions necessary for a platinum oxide formation on the surface of the catalyst under different oxygen partial pressures as well as under reaction conditions. Here, a thin platinum oxide could be found under low oxygen partial pressures (down to 10 mbar), but not under reaction conditions in the presence of CO. Additionally, high pressure X-Ray Photoelectron Spectroscopy (XPS) measurements have been done to identify a possible platinum oxide. A platinum oxide formation under higher oxygen partial pressures and under polarization conditions (NEMCA conditions) could not be found.
Keywords: nemca; epoc; CO oxidation; ethylene oxidation; PtOx formation; ddc:540